The business guide to legal literacy : - Hasl-Kelchner, Hanna (Jossey-Bass, 2006)
This book makes the connection between law, business, decision-making psychology, quality management, organizational change, and leadership and shows how these disciplines influence the company’s legal risk profile. It tackles legal literacy on both the employee and organizational levels and identifies the infrastructure needed to support legal literacy and promote effective communications throughout the organization.